Basic features of generalized anxiety disorder - Antonio W. Zuardi (Medicina, 2017)
This text is addressed to medical undergraduate students with aim to characterize Generalized Anxiety Disorder (GAD) with emphasis on diagnosis and treatment. GAD is one of the most psychiatric disorders under-diagnosed. The main characteristic of GAD is persistent and excessive worry accompanied by physical symptoms related to autonomic hyperactivity and muscle tension. The comorbidity with depression and other anxiety disorders is frequently. The psychotherapeutic approach, in a wide sense, must be a priority in the treatment of this disease and, when indicated, the pharmacological treatment should not be the only therapeutic option